2015
DOI: 10.1093/jb/mvv020
|View full text |Cite
|
Sign up to set email alerts
|

Albumin overload down-regulates integrin-β1 through reactive oxygen species-endoplasmic reticulum stress pathway in podocytes

Abstract: Proteinuria is a major hallmark of glomerular nephropathy and endoplasmic reticulum (ER) stress plays an important role in glomerular nephropathy. The protein levels of integrin-β1 in podocytes are found to be negative correlation with amount of proteinuria. This study investigated whether urinary protein, particularly albumin, induced ER stress that consequently reduced integrin-β1 expression. All experiments were performed using primary cultured rat podocyte. Protein and mRNA expression were measured by west… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 30 publications
0
17
0
1
Order By: Relevance
“…Albumin has been shown to be an ER stress inducer but the underlying mechanisms have not been extensively studied. Others have shown that albumin may provoke inflammasome activation and calcium mobilization in tubular cells while other mechanisms such as reduced expression of the adaptor protein CD2AP, ROS production and activation of the MAPK/caspase‐12 pathway have been reported to be involved in podocyte apoptosis . Of interest, 4‐PBA has been described to decrease fibrosis in chronic proteinuric disease .…”
Section: Discussionmentioning
confidence: 99%
“…Albumin has been shown to be an ER stress inducer but the underlying mechanisms have not been extensively studied. Others have shown that albumin may provoke inflammasome activation and calcium mobilization in tubular cells while other mechanisms such as reduced expression of the adaptor protein CD2AP, ROS production and activation of the MAPK/caspase‐12 pathway have been reported to be involved in podocyte apoptosis . Of interest, 4‐PBA has been described to decrease fibrosis in chronic proteinuric disease .…”
Section: Discussionmentioning
confidence: 99%
“…For example, NF‐kappa B and other pro‐inflammatory transcription factors can induce the activation of downstream integrin β3, leading to podocyte injury and proteinuria . Whereas the expression of integrin β1 in podocyte was considered negatively correlated with the severity of proteinuria . Elevated expression of TGF‐β1 or ROS induced decreased expression of integrin β1, resulting in the production of proteinuria .…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that ER stress is tightly linked to oxidative stress [2,6,20]. Furthermore, it has been shown that AOPP-induced ER stress in adipocytes is mediated by the activation of NADPH oxidasedependent ROS generation [43].…”
Section: Discussionmentioning
confidence: 99%